Adsorption of antibiotics using powdered, granular, and coffee bean activated carbon - Tan, Yuan (2017)
Adsorption isotherm and kinetics of antibiotics using activated carbon are commonly researched but a comparison of adsorption powdered activated carbon (PAC), granular activated carbon (GAC), and powdered coffee bean activated carbon (CBAC) was not adequately evaluated. In this study, adsorption isotherm and kinetics of ampicillin (AMP) and penicillin (PNG) using PAC, GAC, and CBAC are determined by batch adsorption experiment. The results show that PAC and GAC have an R2 value closer to 1 for Langmuir isotherm compared to Freundlich isotherm which implies that PAC and GAC fit Langmuir isotherm while CBAC fit Freundlich isotherm. The kinetic study demonstrated that pseudo-second order describes the rate of adsorption of AMP and PNG using PAC and CBAC. This reflects that the mechanism of adsorption of PAC and CBAC is chemisorption. The mechanism of adsorption for PAC is physisorption due to its R2 value for pseudo-first order is closer to 1 than pseudo-second order. It is concluded that PAC has better adsorption performance compared to GAC and CBAC due to its short equilibrium time.